Characterization Of Coconut Husk As Adsorbent For Methylene Blue Dyes - Rahman, Nurul Natrah Abdul (Universiti Sains Malaysia, 2022)
The dyeing procedure polluted water supplies by depositing dye effluents into them. Amongst the most efficient strategies for decolorization is activated carbon adsorption. Activated carbon coconut husk (ACCH) was developed for methylene blue (MB) reduction in this research. Dyes removal rates were studied using a variety of factors, including pH, temperature, adsorbent dosage, contact time, and initial dye concentration (Oliveira et al., 2020). The optimal treatment pH, dosage of MB and ACCH were determined to be pH 5, 15mg/mL and 1.0g/mL respectively, resulting in MB dye elimination of 84.02%. The impact of initial dye concentration (15mg/mL - 75mg/mL) was studied. As the initial dye concentration and pH rose, so did the adsorption of MB on ACCH. By utilizing the intraparticle diffusion model, the adsorption mechanism was determined. The SEM images results also indicate that the shape of the treated bio adsorbent is more porous and rougher to enhance the adsorption process. EDX images can indicate which element can be found after batch adsorption studies. 82.58% carbon (C), 0.12% aluminium (Al), 11.60% oxygen (O), 4.51% nitrogen (N), silicon (Si), 0.07% sulphur (S), 0.75 % calcium (Ca), and 0.24% phosphorus (P) were detected by element EDX analysis in the ACCH. In the meantime, FTIR examination reveals a decline in peaks due to the elimination of lignin and hemicelluloses. Characteristic of coconut husk based on Iso-electric point (IEP) using Zeta Sizer and X-ray diffraction analysis (XRD) also been studied in this research paper.